Cerium oxide-containing polishing composition as well as preparation method and application thereof

By using a polishing composition containing cerium oxide in the glass grinding and polishing additive, the problems of low abrasive force and high fluidity in the prior art are solved, and efficient polishing effect and longer service life are achieved.

CN119119874APending Publication Date: 2024-12-13BAOTOU TIANJIAO SEIMI POLISHING POWDER CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411277646.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing glass grinding and polishing additives have low abrasive force and high fluidity, resulting in low processing efficiency and short service life, which affects the polishing effect.

Method used

A polishing composition containing cerium oxide, including cerium oxide, water, cellulose compounds, polyamide compounds and organic acids, is prepared by specific dispersion steps to form a high viscosity, high grinding and neutral polishing composition.

Benefits of technology

The viscosity and grinding force of the polishing composition are improved, the polishing time is reduced, the service life is extended, and the adverse effects of chemical corrosion on the polished surface are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040707540000101
    Figure BDA0005040707540000101
  • Figure BDA0005040707540000111
    Figure BDA0005040707540000111
  • Figure BDA0005040707540000112
    Figure BDA0005040707540000112
Patent Text Reader

Abstract

The invention discloses a cerium oxide-containing polishing composition as well as a preparation method and application thereof. The polishing composition comprises the following components in parts by weight: 450-600 parts of cerium oxide, 200-600 parts of water, 0.5-4 parts of a cellulose compound, 6-15 parts of a polyamide-containing compound and 0.2-4 parts of organic acid. The polishing composition has relatively high viscosity and relatively short polishing time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polishing composition containing cerium oxide, a preparation method and application thereof. Background Art

[0002] Abrasive polishing paste is an important additive in the field of surface polishing and plays an important role in glass polishing. With the advancement of science and technology, people's requirements for glass precision are increasing day by day, and the requirements for glass surface performance are getting higher and higher. Therefore, higher requirements are put forward for abrasive polishing additives for glass polishing.

[0003] At present, micron-grade cerium oxide polishing liquid is mainly used in glass grinding and polishing. This grinding and polishing aid uses cerium oxide as an abrasive, has low grinding force, high fluidity of the polishing liquid, low processing efficiency and fast failure.

[0004] CN114507478A discloses a polishing liquid for processing gallium arsenide wafers, which is prepared from the following raw materials in parts by weight: silica sol, dichloroisocyanurate, polyethyleneimine, nano cerium dioxide, fumed silica, a graphene-graphene oxide mixture, hydroxyethyl cellulose, tripolyphosphate or sulfonate.

[0005] CN110437744A discloses a polishing liquid for polishing aluminum nitride substrates, comprising silica colloid, cerium dioxide abrasive, organic amine, oxidant, dispersant, hydroxypropyl methylcellulose, organic silane coupling agent, surfactant, corrosion inhibitor, complexing agent, defoamer, and catalyst. The organic amine is any one of ethylenediamine, triethylamine, ethanolamine, dimethylamine, propylamine, isopropylamine, and cyclohexylamine, and the peroxidant is any one of hydrogen peroxide, sodium hypochlorite, and potassium permanganate. The dispersant is any one of cellulose derivatives, polyacrylamide, dodecyl dimethyl benzyl ammonium bromide, and fatty acid polyethylene glycol ester.

[0006] The above-mentioned polishing liquid has a low viscosity and a high fluidity, which will have an adverse effect on the polishing surface and affect the service life of the polishing slurry. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a polishing composition, which has a higher viscosity and a shorter polishing time. Further, the polishing composition has a higher grinding force. Furthermore, the polishing composition is substantially neutral.

[0008] In one aspect, the present invention provides a polishing composition containing cerium oxide, comprising 450 to 600 parts by weight of cerium oxide, 200 to 600 parts by weight of water, 0.5 to 4 parts by weight of a cellulose compound, 6 to 15 parts by weight of a polyamide-containing compound, and 0.2 to 4 parts by weight of an organic acid;

[0009] The cellulose compound is selected from one or more of cellulose, alkali metal salts of cellulose, cellulose derivatives, and derivatives of alkali metal salts of cellulose;

[0010] The substituents in the cellulose derivative or the derivative of the alkali metal salt of cellulose are selected from one or more of C1-C6 alkyl groups and substituted C1-C6 alkyl groups; the substituents on the C1-C6 alkyl groups are selected from one or more of hydroxyl groups and carboxyl groups;

[0011] The polyamide-containing compound is selected from one or more of polyamide-modified hydrogenated castor oil, polyimide, and polyamide wax;

[0012] The organic acid is selected from alkyl-substituted benzenesulfonic acid, saturated carboxylic acid, and carboxylic acid containing an unsaturated double bond.

[0013] According to the polishing composition of the present invention, preferably, the polishing composition further contains 0.1 to 2.5 parts by weight of a preservative, 0.5 to 6 parts by weight of a dispersant and 0.01 to 0.05 parts by weight of a defoaming agent.

[0014] According to the polishing composition of the present invention, preferably, the alkali metal salt of cellulose can be selected from potassium salt of cellulose or sodium salt of cellulose; the substituent in the cellulose derivative or the derivative of the alkali metal salt of cellulose is selected from one or more of C1-C3 alkyl, substituted C1-C3 alkyl.

[0015] According to the polishing composition of the present invention, preferably, the organic acid is selected from C6-C20 alkyl-substituted benzenesulfonic acid, C1-C6 alkyl carboxylic acid, and C2-C6 unsaturated carboxylic acid.

[0016] According to the polishing composition of the present invention, preferably, the cellulose compound is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, methyl cellulose and hydroxyethyl cellulose.

[0017] According to the polishing composition of the present invention, preferably, the organic acid is selected from one or more of dodecylbenzenesulfonic acid, maleic acid, isobutyric acid, succinic acid and fumaric acid.

[0018] Another invention, the present invention provides a method for preparing the above-mentioned polishing composition, comprising the following steps:

[0019] (1) mixing cerium oxide and water, and then adding a dispersant to mix, to obtain a first dispersed system;

[0020] (2) dispersing the first dispersed system, the cellulose compound and the preservative to obtain a second dispersed system;

[0021] (3) dispersing the second dispersed system and the organic acid to obtain a third dispersed system;

[0022] (4) The third dispersion system is dispersed with a polyamide-containing compound and then dispersed with a defoaming agent to obtain a polishing composition.

[0023] According to the preparation method of the present invention, preferably, step (2) is dispersed at a rotation speed of 1000 to 1500 rpm for 10 to 40 min;

[0024] Step (3) dispersing at a rotation speed of 1000 to 1500 rpm for 2 to 15 minutes;

[0025] In step (4), the third dispersion system and the polyamide-containing compound are dispersed at 1100 to 1800 rpm for 10 to 40 min;

[0026] In step (4), the mixture is dispersed with a defoaming agent at a rotation speed of 1000 to 1500 rpm for 10 to 40 minutes.

[0027] According to the preparation method of the present invention, preferably, the cerium oxide is treated cerium oxide;

[0028] The method also includes the following steps: grinding the cerium oxide raw material and water in a ball mill to obtain ground cerium oxide; and drying the ground cerium oxide to obtain treated cerium oxide.

[0029] In still another aspect, the present invention provides use of the polishing composition in glass polishing.

[0030] The polishing composition of the present invention has a high viscosity, which can reduce the impact and defects on the polishing surface due to high fluidity, increase the service life of the polishing composition, and reduce the amount of the polishing composition. The polishing composition of the present invention has a lower polishing time. Further, the polishing composition of the present invention has a higher grinding force. The polishing composition of the present invention is substantially neutral, which can reduce the adverse effects of chemical corrosion on polishing. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0032] <Polishing Composition>

[0033] The polishing composition of the present invention comprises cerium oxide, water, a cellulose compound, a polyamide-containing compound and an organic acid. In certain embodiments, it further comprises a preservative, a dispersant and a defoaming agent. Preferably, the polishing composition consists of the above components.

[0034] The amount of cerium oxide used is 450 to 600 parts by weight, preferably 470 to 565 parts by weight. The amount of cerium oxide used can be 500 to 515 parts by weight, 540 to 550 parts by weight, or 490 to 500 parts by weight. The cerium oxide can be micron-sized cerium oxide.

[0035] The amount of water used is 200 to 600 parts by weight, preferably 210 to 570 parts by weight, 410 to 425 parts by weight, 350 to 360 parts by weight, or 210 to 220 parts by weight.

[0036] The cellulose compound is one or more selected from cellulose, alkali metal salts of cellulose, cellulose derivatives, and derivatives of alkali metal salts of cellulose.

[0037] The alkali metal salt of cellulose may be one or more of a potassium salt of cellulose and a sodium salt of cellulose.

[0038] The substituent of the cellulose derivative or the derivative of the alkali metal salt of cellulose is selected from one or more of C1-C6 alkyl, substituted C1-C6 alkyl. Preferably, it is selected from C1-C3 alkyl, substituted C1-C3 alkyl. The substituent is selected from one or more of hydroxyl and carboxyl.

[0039] Examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, butyl, methylpropyl, pentyl, methylbutyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, ethylbutyl.

[0040] Examples of substituted alkyl groups include, but are not limited to, hydroxymethyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, hydroxymethylpropyl, methylhydroxypropyl, hydroxypentyl, hydroxymethylbutyl, methylhydroxybutyl, hydroxyethylpropyl, ethylhydroxypropyl, hydroxyhexyl, hydroxymethylpentyl, methylhydroxypentyl, dimethylhydroxybutyl, hydroxyethylbutyl, ethylhydroxybutyl, carboxymethyl, carboxyethyl, carboxypropyl, carboxybutyl, carboxymethylpropyl, methylcarboxypropyl, carboxypentyl, carboxymethylbutyl, methylcarboxybutyl, carboxyethylpropyl, ethylcarboxypropyl, carboxyhexyl, carboxymethylpentyl, methylcarboxypentyl, dimethylcarboxybutyl, carboxyethylbutyl, and ethylcarboxybutyl.

[0041] Preferably, the cellulose compound is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, methyl cellulose and hydroxyethyl cellulose.

[0042] The amount of the cellulose compound used is 0.5 to 4 parts by weight, preferably 0.8 to 2.8 parts by weight, 0.8 to 0.9 parts by weight, 1.2 to 1.3 parts by weight, and 1.7 to 1.8 parts by weight.

[0043] The polyamide-containing compound is selected from one or more of polyamide-modified hydrogenated castor oil, polyimide, and polyamide compounds.

[0044] The polyamide-modified hydrogenated castor oil may be polyamide-modified hydrogenated castor oil with a brand name of CRAYVALLAC MT produced by Arkema Company of France.

[0045] The polyimide may be a polyimide with a brand name of PI produced by Dongguan Zhanyang Polymer Materials Co., Ltd.

[0046] The polyamide wax may be a polyamide wax with a brand name of Crayvallac ULTRA produced by Arkema of France.

[0047] The amount of the polyamide compound is 6 to 15 parts by weight, preferably 8 to 14 parts by weight, 8 to 9 parts by weight, 9 to 10 parts by weight, or 13 to 14 parts by weight.

[0048] The organic acid is selected from alkyl-substituted benzenesulfonic acid, saturated carboxylic acid, and carboxylic acid containing unsaturated double bonds. The saturated carboxylic acid may be a monocarboxylic acid or a dicarboxylic acid. The unsaturated carboxylic acid may be a monocarboxylic acid or a dicarboxylic acid. Preferably, the organic acid is selected from C6-C20 alkyl-substituted benzenesulfonic acid, C1-C6 alkyl carboxylic acid, and C2-C6 unsaturated carboxylic acid. More preferably, the organic acid is selected from C10-C15 alkyl-substituted benzenesulfonic acid, C3-C5 alkyl carboxylic acid, and C3-C5 unsaturated carboxylic acid.

[0049] Examples of alkyl-substituted benzenesulfonic acids include, but are not limited to, decanedioic acid, undecylbenzenesulfonic acid, dodecylbenzenesulfonic acid, tridecylbenzenesulfonic acid, tetradecylbenzenesulfonic acid, pentadecylbenzenesulfonic acid. Examples of saturated carboxylic acids include, but are not limited to, propionic acid, isopropionic acid, butyric acid, isobutyric acid, succinic acid. Examples of carboxylic acids containing unsaturated double bonds include, but are not limited to, maleic acid, fumaric acid.

[0050] The amount of organic acid used is 0.2 to 4 parts by weight, preferably 0.5 to 2.8 parts by weight, 1.8 to 2.5 parts by weight, or 2 to 2.2 parts by weight.

[0051] The amount of the preservative is 0.1 to 2.5 parts by weight, preferably 0.3 to 2 parts by weight. The preservative can be 0.6 to 0.8 parts by weight, or 0.4 to 0.5 parts by weight. The preservative can be sodium benzoate.

[0052] The amount of the dispersant is 0.5 to 6 parts by weight, preferably 1.5 to 5 parts by weight, and more preferably 2 to 3 parts by weight. The dispersant can be selected from one or more of sodium polyacrylate, polyacrylamide, sodium polycarboxylate, polyvinyl alcohol, N-methylpyrrolidone, and sorbitan monooleate polyoxyethylene ether.

[0053] The amount of the defoamer is 0.01 to 0.05 parts by weight, preferably 0.015 to 0.025 parts by weight, and more preferably 0.018 to 0.02 parts by weight. The defoamer can be selected from one or more of modified polysiloxane, polymethyl alkyl siloxane, and polyether modified polydimethyl siloxane. The defoamer can be selected from BYK-018, BYK-085, or BYK-019.

[0054] <Preparation Method of Polishing Composition>

[0055] The method for preparing the polishing composition of the present invention comprises the following steps: (1) forming a first dispersion system; (2) forming a second dispersion system; (3) forming a third dispersion system; and (4) obtaining the polishing composition.

[0056] Step of forming a first dispersed system

[0057] Cerium oxide and water are mixed, and then a dispersant is added and mixed to obtain a first dispersed system.

[0058] The cerium oxide may be treated cerium oxide. The method may further include the following steps: grinding the cerium oxide raw material and water in a ball mill to obtain ground cerium oxide; and drying the ground cerium oxide to obtain treated cerium oxide.

[0059] The mass ratio of the cerium oxide raw material to water may be 1:(0.6-1.8); preferably 1:(0.8-1.5); and more preferably 1:(1-1.2).

[0060] The grinding time may be 1 to 5 hours; preferably 2 to 4 hours; more preferably 2.5 to 3 hours.

[0061] The drying temperature may be 100 to 180° C., preferably 110 to 160° C., and more preferably 120 to 150° C. The drying time may be 1 to 5 hours, and preferably 2 to 4 hours.

[0062] Step of forming a second dispersed system

[0063] The first dispersion system, the cellulose compound and the preservative are dispersed to obtain a second dispersion system.

[0064] Dispersion can be carried out in a dispersion pan.

[0065] The dispersion can be carried out at a rotation speed of 1000 to 1500 rpm; preferably, the dispersion is carried out at a rotation speed of 1100 to 1400 rpm. In certain embodiments, the dispersion is carried out at a rotation speed of 1200 to 1300 rpm.

[0066] The dispersion time may be 10 to 30 min, preferably 15 to 25 min, and more preferably 20 to 25 min.

[0067] Steps for forming the third dispersed system

[0068] The second dispersed system and the organic acid are dispersed to obtain a third dispersed system.

[0069] Dispersion can be carried out in a dispersion pan.

[0070] The dispersion can be carried out at a rotation speed of 1000 to 1500 rpm; preferably, the dispersion is carried out at a rotation speed of 1100 to 1400 rpm. In certain embodiments, the dispersion is carried out at a rotation speed of 1200 to 1300 rpm.

[0071] The dispersion time may be 2 to 15 minutes, preferably 5 to 10 minutes. In certain embodiments, the dispersion time is 7 to 8 minutes.

[0072] Step of obtaining a polishing composition

[0073] The third dispersion system is dispersed with the polyamide-containing compound and then dispersed with the defoaming agent to obtain a polishing composition.

[0074] The third dispersion system and the polyamide-containing compound can be dispersed at 1100-1800 rpm; preferably, the third dispersion system and the polyamide-containing compound are dispersed at 1200-1600 rpm. In some embodiments, the third dispersion system and the polyamide-containing compound are dispersed at 1300-1500 rpm.

[0075] The dispersion time of the third dispersion system and the polyamide-containing compound can be 10 to 40 minutes, preferably 20 to 30 minutes, and more preferably 20 to 25 minutes.

[0076] The dispersion is carried out with the defoaming agent at a rotation speed of 1000 to 1500 rpm; preferably, the dispersion is carried out with the defoaming agent at a rotation speed of 1100 to 1400 rpm; more preferably, the dispersion is carried out with the defoaming agent at a rotation speed of 1200 to 1300 rpm.

[0077] The dispersion time with the defoaming agent can be 10 to 40 minutes, preferably 20 to 30 minutes, and more preferably 20 to 25 minutes.

[0078] <Use of polishing composition>

[0079] The polishing composition of the present invention has a good polishing effect on glass. Therefore, the present invention provides the use of the polishing composition in glass polishing. The glass can be 40J-SFH2 glass produced by Nippon Koh Glass Co., Ltd.

[0080] Here are the raw materials:

[0081] The polyamide-modified hydrogenated castor oil was CRAYVALLAC MT, purchased from Arkema, France.

[0082] The polyimide brand is PI, which was purchased from Dongguan Zhanyang Polymer Materials Co., Ltd.

[0083] The polyamide wax is Crayvallac ULTRA, purchased from Arkema, France.

[0084] The modified polysiloxane was purchased from BYK Chemicals with the brand number of BYK-018.

[0085] The polymethyl alkyl siloxane was purchased from BYK-085.

[0086] The polyether-modified polydimethylsiloxane is BYK-019, purchased from BYK Chemicals. The test method is described below:

[0087] Viscosity of the polishing composition: The viscosity of the polishing composition was measured using a NDJ-8S digital viscometer.

[0088] Grinding force: Take the polishing composition in the amount shown in Table 2, add pure water, dilute to 7.5% concentration, and use UNIPOL-1200S grinding and polishing machine of Shenyang Kejing Automation Equipment Co., Ltd. to polish the lens. Set the pressure to 6.0kg, the turntable speed to 60rpm for the upper motor and 40rpm for the lower motor. The polishing time is set as shown in Table 2, and the grinding force of the polishing composition is tested by measuring the mass difference of the lens before and after polishing.

[0089] Example 1

[0090] The CeO2 raw material and deionized water A were placed in a ball mill and ground for 2.5 h to obtain ground CeO2.

[0091] The ground CeO2 is dried in an oven at 120°C for 3 hours to obtain treated CeO2. The treated CeO2 is mixed with deionized water B, and then a dispersant is added and mixed to obtain a first dispersed system.

[0092] The first dispersed system, the cellulose compound and sodium benzoate are dispersed on a dispersion disk at a rotation speed of r1 for a time of t1 to obtain a second dispersed system.

[0093] The second dispersed system and the organic acid are dispersed on a dispersion disk at a rotation speed of r2 for a time of t2 to obtain a third dispersed system.

[0094] The third dispersion system is dispersed with the polyamide-containing compound at a rotation speed of r3 for a time of t3, and then dispersed with the defoaming agent at a rotation speed of r4 for a time of t4 to obtain a polishing composition.

[0095] The selection and dosage of each raw material, as well as the process parameters are shown in Tables 1-1 to 1-3. The properties of the polishing composition are shown in Table 2.

[0096] Table 1-1

[0097]

[0098]

[0099] Table 1-2

[0100]

[0101]

[0102] Table 1-3

[0103]

[0104] Note: The unit of the amount of each substance in the above table is part by weight; deionized water A and deionized water B both represent deionized water, and A and B are only used to distinguish the two.

[0105] Comparative Example

[0106] (1) Cerium oxide and water in a mass ratio of 1:5 were ground in a ball mill for 2 h, and then dried at 150° C. for 3 h to obtain treated cerium oxide.

[0107] The treated cerium oxide and water are mixed at a mass ratio of 1:1, and sodium polycarboxylate is added and mixed to obtain a first dispersion system. The amount of sodium polycarboxylate used is 3% of the mass of the cerium oxide.

[0108] (2) The first dispersion system and sodium benzoate are dispersed at a dispersion rate of 1150 rpm for 20 minutes to obtain a second dispersion system. The amount of sodium benzoate used is 0.2% of the mass of cerium oxide.

[0109] (3) The second dispersion system and dodecylbenzenesulfonic acid were dispersed at a dispersion rate of 1150 rpm for 10 minutes to obtain a third dispersion system. The amount of dodecylbenzenesulfonic acid added was 0.25% of the mass of cerium oxide.

[0110] (4) The third dispersion system and modified polysiloxane were dispersed at a dispersion rate of 1150 rpm for 20 minutes to obtain a polishing composition containing cerium oxide. The amount of modified polysiloxane used was 0.2% of the mass of cerium oxide.

[0111] Table 2

[0112]

[0113]

[0114] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A polishing composition containing cerium oxide, characterized in that The polishing composition comprises 450 to 600 parts by weight of cerium oxide, 200 to 600 parts by weight of water, 0.5 to 4 parts by weight of a cellulose compound, 6 to 15 parts by weight of a polyamide-containing compound and 0.2 to 4 parts by weight of an organic acid; The cellulose compound is selected from one or more of cellulose, alkali metal salts of cellulose, cellulose derivatives, and derivatives of alkali metal salts of cellulose; The substituents in the cellulose derivative or the derivative of the alkali metal salt of cellulose are selected from one or more of C1-C6 alkyl groups and substituted C1-C6 alkyl groups; the substituents on the C1-C6 alkyl groups are selected from one or more of hydroxyl groups and carboxyl groups; The polyamide-containing compound is selected from one or more of polyamide-modified hydrogenated castor oil, polyimide, and polyamide wax; The organic acid is selected from alkyl-substituted benzenesulfonic acid, saturated carboxylic acid, and carboxylic acid containing an unsaturated double bond.

2. The polishing composition according to claim 1, characterized in that The polishing composition also contains 0.1 to 2.5 parts by weight of a preservative, 0.5 to 6 parts by weight of a dispersant and 0.01 to 0.05 parts by weight of a defoaming agent.

3. The polishing composition according to claim 1, characterized in that The alkali metal salt of cellulose can be selected from potassium salt of cellulose or sodium salt of cellulose; the substituent in the cellulose derivative or the derivative of the alkali metal salt of cellulose can be selected from one or more of C1-C3 alkyl, substituted C1-C3 alkyl.

4. The polishing composition according to claim 1, characterized in that The organic acid is selected from C6-C20 alkyl-substituted benzenesulfonic acid, C1-C6 alkyl carboxylic acid, and C2-C6 unsaturated carboxylic acid.

5. The polishing composition according to claim 1, characterized in that The cellulose compound is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, methyl cellulose and hydroxyethyl cellulose.

6. The polishing composition according to claim 1, characterized in that The organic acid is selected from one or more of dodecylbenzenesulfonic acid, maleic acid, isobutyric acid, succinic acid and fumaric acid.

7. The method for preparing the polishing composition according to claim 2, characterized in that: The steps include: (1) mixing cerium oxide and water, and then adding a dispersant to mix, to obtain a first dispersed system; (2) dispersing the first dispersed system, the cellulose compound and the preservative to obtain a second dispersed system; (3) dispersing the second dispersed system and the organic acid to obtain a third dispersed system; (4) The third dispersion system is dispersed with a polyamide-containing compound and then dispersed with a defoaming agent to obtain a polishing composition.

8. The preparation method according to claim 7, characterized in that: Step (2) dispersing at a rotation speed of 1000 to 1500 rpm for 10 to 40 minutes; Step (3) dispersing at a rotation speed of 1000 to 1500 rpm for 2 to 15 minutes; In step (4), the third dispersion system and the polyamide-containing compound are dispersed at 1100 to 1800 rpm for 10 to 40 min; In step (4), the mixture is dispersed with a defoaming agent at a rotation speed of 1000 to 1500 rpm for 10 to 40 minutes.

9. The preparation method according to claim 7, characterized in that: The cerium oxide is treated cerium oxide; The method also includes the following steps: grinding the cerium oxide raw material and water in a ball mill to obtain ground cerium oxide; and drying the ground cerium oxide to obtain treated cerium oxide.

10. Use of the polishing composition according to any one of claims 1 to 6 in glass polishing.

Citation Information

Cited By

  • Joint filling glue material without sagging on vertical surface and preparation method thereof

    CN121160277A